Annulus formation on scales and seasonal growth of the Central Amazonian anostomid Schizodon fasciatus - Fabré, Nídia Noemí; Saint-Paul, Ulrich (Journal of Fish Biology, 1998)
Annulus formation on the scales of the Central Amazonian anastomid fish Schizodon fasciatus was studied with respect to periodic variations in growth rates caused by seasonal inundation or associated biological processes. Monthly samples from fish markets were analysed with regard to marginal scale increment, feeding index, condition factor, gonadosomatic index, and body cavity fat content. There was a significant variation in all indices which was related to seasonal change in water level. Fat storage was related to energy requirements especially during gonad maturation. Fastest growth was observed during the period of falling water level. The formation of scale growth marks corresponded to the period of gonad maturation between January and February. The results indicate the formation of only one single growth mark on scales per year.
Keywords: Annulus Formation; Growth; Inundation; Scale; Seasonality; South America, Amazonia; Schizodon Fasciatus